The dead zone - King, Stephen, 1947- (New York : Signet, 1980)
An accident has left John Smith in a coma for four years. When he awakens he finds he is able to discern information about others simply by touching them.
Booklist.
Library Journal.
Wilson's Fiction.
Adult
Keywords: Coma -- Patients -- Fiction; Extrasensory perception -- Fiction; Coma -- Patients -- Fiction; Extrasensory perception -- Fiction; Horror fiction